Epac induces ryanodine receptor-dependent intracellular and inter-organellar calcium mobilization in mpkCCD cells - Yip, Kay-Pong; Ribeiro-Silva, Luisa; Cha, Byeong; Rieg, Timo; Sham, James S. K. (Frontiers in Physiology, 2023)
Arginine vasopressin (AVP) induces an increase in intracellular Ca2+ concentration ([Ca2+]i) with an oscillatory pattern in perfused kidney inner medullary collecting duct (IMCD). AVP-induced Ca2+ mobilization in inner medullary collecting duct is essential for apical exocytosis and is mediated by the exchange protein directly activated by cAMP (Epac). mpkCCD cell is the cell model used for transcriptomic and phosphoproteomic studies of AVP signaling in kidney collecting duct. The present study examined the characteristics of Ca2+ mobilization in mpkCCD cells, and utilized mpkCCD as a model to investigate the Epac-induced intracellular and intra-organellar Ca2+ mobilization. Ca2+ mobilization in cytosol, endoplasmic reticulum lumen, and mitochondrial matrix were monitored with Ca2+ fluorescent probe and site-specific Ca2+ biosensors. Images of mpkCCD cells and perfused inner medullary duct were collected with confocal microscopy. Cell permeant ligands of ryanodine receptors (RyRs) and inositol 1,4,5 trisphosphate receptors (IP3Rs) both triggered increase of [Ca2+]i and Ca2+ oscillations in mpkCCD cells as reported previously in IMCD. The cell permeant Epac-specific cAMP analog Me-cAMP/AM also activated robust Ca2+ mobilization and oscillations in mpkCCD cells. Using biosensors to monitor ER luminal Ca2+ or mitochondrial matrix Ca2+, Me-cAMP/AM not only triggered Ca2+ release from ER into cytoplasm, but also shuttled Ca2+ from ER into mitochondria. Epac-agonist induced synchronized Ca2+ spikes in cytosol and mitochondrial matrix, with concomitant declines in endoplasmic reticulum luminal Ca2+. Me-cAMP/AM also effectively triggered store-operated Ca2+ entry (SOCE), suggesting that Epac-agonist is capable of depleting ER Ca2+ stores. These Epac-induced intracellular and inter-organelle Ca2+ signals were mimicked by the RyR agonist 4-CMC, but they were distinctly different from IP3R activation. The present study hence demonstrated that mpkCCD cells retain all reported features of Ca2+ mobilization observed in perfused IMCD. It further revealed information on the dynamics of Epac-induced RyR-dependent Ca2+ signaling and ER-mitochondrial Ca2+ transfer. ER-mitochondrial Ca2+ coupling may play a key role in the regulation of ATP and reactive oxygen species (ROS) production in the mitochondria of renal tubule. mpkCCD cells can serve as a renal cell model to address novel questions of how mitochondrial Ca2+ regulates cytosolic Ca2+ signals, inter-organellar Ca2+ signaling, and renal tubular functions.